Violence, anomie and adolescence - Vásquez Bermejo, Óscar (2003)
The growing anomic violence, along with the processes of industrialization and urbanization in modern societies, constitutes the main contemporary problem. According to the IDB, Latin America is the region, in addition to being unequal, the most violent in the world; devotes more than 14% of the GDP to the problems of urban violence, this being the main factor that affects its development possibilities.